Eco-enzyme Apple Bar Soap for Skin Hydration in Older Adults - Vinsur, Elizabeth Yun Yun; Sipollo, Berliany Venny (Babali Nursing Research, 2025)
Introduction: This study investigated the effect of bar soap made from eco-enzymes and apples on the skin moisture of older adults. Eco-enzymes, produced by fermenting organic materials, have a pH of 4-5. Apples contain skin-beneficial compounds: fiber, antioxidants, vitamins, minerals, and phytonutrients. This research aimed to determine the impact of using this soap on the moisture of older adults' skin.   Methods: A quasi-experimental pre-test/post-test design was used with a treatment group (n=33) using the soap for 7 days and a control group (n=33) receiving no intervention. The study was conducted on older adults who met the inclusion criteria. Skin moisture was measured using a digital skin analyzer and analyzed with a Wilcoxon test. Results: The results indicated no significant effect of the soap on skin moisture in either the treatment (p=0.063) or control (p=0.083) groups (p>0.05). The unexpected results were attributed to the short study duration and extreme weather conditions at the mountain's base. Conclusion: Given the challenging weather at the mountain's base, further research is necessary, with adjustments to the soap formula, a more extended research time, and a larger sample size.